TINJAUAN KARAKTER SHELTER SEMENTARA SEBAGAI UPAYA MITIGASI BENCANA BAGI KORBAN BENCANA ALAM - Nadhifia Iryadini R.A; Gregorius Prasetyo Adhitama (Serat Rupa: Journal of Design, 2021)
Indonesia is a country with high potential against the threat of natural disasters. Badan Nasional Penanggulangan Bencana (BNPB) noted that the number of natural disasters occurring during 2018-2019 has increased. Many lost their homes, property, and public facilities. It has a direct impact on the psychological condition of the victim, therefore temporary shelters are urgently needed by the victims after the disaster. Shelter has an important role to play in reducing the risk of death and vulnerability and strengthening community resilience. Temporary shelter is intended as one of the recovery efforts that bridges the transition period between the emergency response phase and the reconstruction period completed. The provision of temporary shelter is expected to alleviate the suffering of disaster victims and protect victims from future disasters, but the needs and rights of many victims are not fulfilled. This research aims to explain and produce findings related to the character of temporary shelters for victims of natural disasters in meeting the needs of their residents. In this research the authors used descriptive qualitative methods. Data collection is done by observation techniques, interviews and through secondary data. The process of data analysis method is done by comparing each aspect studied and looking at the pattern of relationship then linking the findings with disaster mitigation efforts. Analysis of the structure of space relationships is done by the Space Syntax analysis method. The results of this research produced a variety of temporary shelter characters, among others are aspects of type and shape, the results found that there are 2 organizations of shapes applied to temporary shelters, namely linear shapes and classified shapes, shelter sizes meet the capacity needs for one family (4-5 people), then the space programs applied are private spaces and public spaces , while in the accessibility aspect, there are 3 types of space configurations that result in that space A (public space) has easy access to, building materials used are natural materials and building materials, as well as in construction systems using earthquake-resistant building systems and knockdown systems so that they can be dismantled because of their temporary nature.